Effects of a short‐term supranutritional selenium supplementation on redox balance, physiology and insulin‐related metabolism in heat‐stressed pigs. Issue 1 (16th March 2017) - Liu, F.; Celi, P.; Cottrell, J. J.; Chauhan, S. S.; Leury, B. J.; Dunshea, F. R.
Summary: Heat stress (HS) disrupts redox balance and insulin‐related metabolism. Supplementation with supranutritional amounts of selenium (Se) may enhance glutathione peroxidase (GPX) activity and reduce oxidative stress, but may trigger insulin resistance. Therefore, the aim of this experiment was to investigate the effects of a short‐term high Se supplementation on physiology, oxidative stress and insulin‐related metabolism in heat‐stressed pigs. Twenty‐four gilts were fed either a control (0.20 ppm Se) or a high Se (1.0 ppm Se yeast, HiSe) diet for 2 weeks. Pigs were then housed in thermoneutral (20°C) or HS (35°C) conditions for 8 days. Blood samples were collected to study blood Se and oxidative stress markers. An oral glucose tolerance test (OGTT) was conducted on day 8 of thermal exposure. The HS conditions increased rectal temperature and respiration rate (both p  < .001). The HiSe diet increased blood Se by 12% ( p  < .05) and ameliorated the increase in rectal temperature ( p  < .05). Heat stress increased oxidative stress as evidenced by a 48% increase in plasma advanced oxidized protein products (AOPPs; p  < .05), which may be associated with the reductions in plasma biological antioxidant potential (BAP) and erythrocyte GPX activity (both p  < .05). The HiSe diet did not alleviate the reduction in plasma BAP or increase in AOPPs observed during HS, although it tended to increase erythrocyte GPX activity by 13% ( p  = .068). Without affecting insulin, HS attenuated lipid mobilization, as evidenced by a lower fasting NEFA concentration ( p  < .05), which was not mitigated by the HiSe diet. The HiSe diet increased insulin AUC, suggesting it potentiated insulin resistance, although this only occurred under TN conditions ( p  = .066). In summary, HS induced oxidative stress and attenuated lipid mobilization in pigs. The short‐term supranutritional Se supplementation alleviated hyperthermia, but did not protect against oxidative stress in heat‐stressed pigs.